1961
DOI: 10.1152/ajplegacy.1961.200.6.1197
|View full text |Cite
|
Sign up to set email alerts
|

Species differences in effect of gram-negative endotoxin on circulation

Abstract: Studies were made in 5 monkeys, 7 rabbits, and 33 cats of the effect of gram-negative endotoxin on aortic, pulmonary artery (PAP), and portal venous (PVP) pressures; and on changes in weight of a short segment of intestine. Studies of blood pooling were also made in 12 cats. The responses in these species were compared with those previously observed in the dog. Although variable degrees of hypotension developed at one time or another in all animals following injection of endotoxin, the early precipitous hypote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

1969
1969
1980
1980

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(30 citation statements)
references
References 0 publications
4
26
0
Order By: Relevance
“…Kulda and others (Kuida et al, 1961) observed that the pr'mate lung was markedly affected by the administration of endotoxin. Reported pulmonary pathological alterationg have varied due to prominent species differences ob-L served In the reaction to endotoxin.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Kulda and others (Kuida et al, 1961) observed that the pr'mate lung was markedly affected by the administration of endotoxin. Reported pulmonary pathological alterationg have varied due to prominent species differences ob-L served In the reaction to endotoxin.…”
Section: Introductionmentioning
confidence: 97%
“…Differences have also been observed betwee,, experiments utilizing a single injection of endotoxhi and those involvIng the generalized Shwartzman phenomenon (Wong, 1962;McKay et al, 1966;Horn and Collins, 1968b). Abnormal pulmonary hemodynamics and morphology following a single injection of endotoxin In dogs have been reported (Kuida et al, 1961;Harrison et al, 1969). Pulmonary changes after endotoxin in rats or rabbits Include platelet'agglutination within pulmonary capillaries (Stetson, 1951;McKay et al, 1966), rupture of capillary walls (DePalma et al, 1967), fibrin deposition (McKay et al, 1966;DePalfra et al, 1967), clumps of polymorphonuclear leukocytes (Stetson, 1951;DePalma et al, 1967;Horn and Collins, 1968b), and polymorphonuclear leukocyte fragmentation withIn the lung capillaries (McKay et al, 1966;Horn and Collins, 1968b).…”
Section: Introductionmentioning
confidence: 99%
“…Their methods, however, are 100-fold less sensitive than those presently in use in our laboratory and are inadequate to measure the levels of bradykinin spontaneously generated during endotoxemia. The dog clearly responds differently to acute endotoxemia than does the primate (22,23). In addition, the kinin-generating systems of the dog have different specificities than those of the primate (24).…”
Section: Discussionmentioning
confidence: 97%
“…Utilization of this cobra factor (CoF)1 made feasible in vivo studies of the influence of complement depletion on experimental gram-negative bacillary bacteremia. A subhuman primate was utilized to approximate human physiologic responses (22)(23)(24)(25)(26)(27)(28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%